ANALISIS GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK KONVENSIONAL YANG TERDAPAT PADA BURSA EFEK INDONESIA PERIODE 2016-2019 - Novi Purnamasari; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine how the influence of Good Corporate Governance on conventional bank financial performance. Variables of Good Corporate Governance are the independent board of commissioners, the board of directors, the audit committee, managerial ownership and institutional ownership, and one dependent variable, financial performance. This study used secondary data, the population taken in this study are all conventional banks listed on the Indonesia Stock Exchange and using purposive sampling method. The test used multiple linear regression test. The results in this study indicate that simultaneously the independent board of commissioners, board of directors, audit committee, managerial ownership and institutional ownership affect the financial performance of conventional banks.Keywords: Independent board of commissioners, Board of directors, Audit committee, Managerial Ownership, Institutional Ownership, Financial performance.